The Effect of Internal Audit, Internal Control and Audit Committee on Fraud Prevention (Case Study at Bank Mandiri Jakarta Tanjung Priok Area) - Putri, Dini Septiani; Wahyuni, Putri Dwi (Journal of Economics, Bussiness and Management Issues, 2024)
Fraud has often occurred in the corporate environment. Fraud is usually based on personal, group or business interests. The economic crisis has encouraged corporate fraud, especially due to the weak implementation of internal control and corporate governance in the banking industry. In an effort to prevent fraud, companies can consistently empower the role of the company's internal auditors who can trigger the implementation of management risk control, internal control systems, and audit committees which have an important role in various aspects of the organization including fraud prevention. This study aims to examine the influence of the role of internal audit, internal control, and the audit committee on fraud prevention. The population in this study used 7 of the 25 Bank Mandiri Branch Offices in the Tanjung Priok Enggano Area, with a total of 85 respondents. The data collection method used a questionnaire by giving a score value according to the Likert scale measurement system . This type of research used quantitative research with a case study method. The sampling technique used purposive sampling. The data analysis method used is multiple linear regression with the SPSS version 25 application. The results show that internal auditing, internal control, and audit committees have a significant effect on fraud prevention.